Turkish Science Teacher Candidates Understandings of Equitable Assessment and Their Plans about It - Kemal Izci (Journal of Education in Science, Environment and Health)
This study aims to investigate how Turkish science teacher candidates understand equitable assessment and in what ways they plan to provide equitable assessment practices. 156 science teacher candidates from a teacher education program in a large university in Eastern part of Turkey participated in the current study. A questionnaire and semi-structured interviews served as data sources. All collected data were qualitatively analyzed to illustrate science teacher candidates’ understandings of equitable assessment and their plans to achieve equitable assessment in their lessons. Results of the study showed that science teacher candidates mostly equated equitable assessment with fairness including fairness in grading. But most of the teacher candidates did not consider that providing equal opportunities for students to display their levels of understanding about the related concepts was not an important characteristic of equitable assessment. The results also showed that participants focused on differences in learning styles and language as reasons why to provide equitable assessment and accordingly stated some ways to achieve equality in assessment processes for these groups. While preparing teachers, teacher education programs need to emphasize more understanding of diversity and provide the knowledge and attitudes necessary for effective teaching.